Young Adults' Mental Health Status: Investigating GERD's Relationship with Anxiety and Depression - Annabih, Muhammad Fikri; Putri, Mustika Anggiane (Biomedical Journal of Indonesia, 2025)
Introduction. Gastroesophageal Reflux Disease (GERD) is a chronic digestive disorder that occurs when stomach acid or, occasionally, stomach contents flow back (reflux) into the esophagus. This backwash (acid reflux) can irritate the lining of the esophagus, causing uncomfortable symptoms and potential complications. studies suggest that smoking, obesity, anxiety/depression, and older age are some of the contributing factors to GERD development. Young adults in Jakarta showed a 7.5% GERD prevalence rate during 2017. This research explores the potential correlation between anxiety and depression with GERD development in young adult populations. Methods. This study utilized a cross-sectional method to assess the symptoms of anxiety, depression, and GERD using the Hospital Anxiety and Depression Scale (HADS) questionnaire and GERD Questionnaire (GERDQ). The research involved 115 participants aged 18-40 from Pondokkaso Urban Village. The study analyzed gender, anxiety, depression, and Gerd using Fisher Exact tests (p<0.05). Results. Analysis of 115 respondents revealed GERD prevalence in 26 subjects (22.6%), anxiety in 5 subjects (4.3%), and depression in 6 subjects (5.2%). Statistical analysis demonstrated no significant correlation between anxiety (p=1.000), depression (P=0.128), or gender and GERD incidence (P=0.756) among young adult subjects. Conclusions. Statistical analysis revealed no significant correlation between GERD incidence and the variables of anxiety, depression, and gender among young adults in Pondokkaso Urban Village.